Tinjauan Islam Tentang Praktek Hybrid Contract Pada Perusahaan Otobus Handoyo - Fatah , Abdul (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
PO Handoyo is a bus company with a unique innovation, namely the implementation of a hybrid contract. One of the hybrid contract practices implemented by POs. Handoyo is the purchase of bus tickets including meals. Hybrid contract is an agreement between two parties to carry out a contract in which there are two or more contracts. This research aims to provide an understanding of what a Hybrid Contract is, and how it is practiced at PO Handoyo, as well as how the Islamic view of the application of the Hybrid Contract on buying trans Java-Sumatra bus tickets includes eating at PO Handoyo. The type of research used in this study is qualitative and literature using primary and secondary data sources. The results of this study are that the application of hybrid contracts in purchasing trans Java-Sumatra bus tickets including is a permissibility and does not belong to multiple contracts which are forbidden.